CASPASE IN PEPTIC ULCER - Meigita Indah Farkhani; Jutti Levita (Jurnal Ilmiah Farmako Bahari, 2022)
Peptic ulcer disease (PUD) is when gastric mucosa gets injured due to the increase of gastric acid and the pepsin enzyme. The common risk factors are the infection of Helicobacter pylori bacteria and the misused of NSAIDs. This review article aims to describe the role of caspase in PUD. Methods used are the selection of articles in PubMed. Caspase is a protease enzyme that plays an apoptotic and inflammatory reaction that can be activated when dimerized or cleaved. Caspase-3, caspase-6, caspase-7, caspase-8, and caspase-9 are divided into two subgroups for the apoptotic group. Caspase-1, caspase 4, and caspase-5 are part of inflammation group. Some compounds can inhibit modulateit. Moreover, most of them work for being inhibitors to avoid PUD. Caspase-1 holds a high responsibility to activate other caspases.